Elephant grass clones for silage production (Scientia Agricola, 2013)
Ensiling warm-season grasses often requires wilting due to their high moisture content, and the presence of low-soluble sugars in these grasses usually demands the use of additives during the ensiling process. This study evaluated the bromatological composition of the fodder and silage from five Pennisetum sp. clones (IPA HV 241, IPA/UFRPE Taiwan A-146 2.114, IPA/UFRPE Taiwan A-146 2.37, Elephant B, and Mott). The contents of 20 Polyvinyl chloride (PVC) silos, which were opened after 90 days of storage, were used for the bromatological analysis and the evaluation of the pH, nitrogen, ammonia, buffer capacity, soluble carbohydrates, and fermentation coefficients. The effluent losses, gases and dry matter recovery were also calculated. Although differences were observed among the clones (p < 0.05) for the concentrations of dry matter, insoluble nitrogen in acid detergents, insoluble nitrogen in neutral detergents, soluble carbohydrates, fermentation coefficients, and in vitro digestibility in the forage before ensiling, no differences were observed for most of these variables after ensiling. All of the clones were efficient in the fermentation process. The IPA/UFRPE TAIWAN A-146 2.37 clone, however, presented a higher dry matter concentration and the best fermentation coefficient, resulting in a better silage quality, compared to the other clones.